Habitat and Food of Vampire Crabs (Geosesarma sp.) in Menoreh Mountain, Yogyakarta, Indonesia - Kurniawan, Tito; Waluyo; Nofreeana, Andri; Tri Aji, Muhammad (Media Konservasi, 2025)
Vampire crabs (Geoseserma sp.) are freshwater crabs that inhabit humid tropical forest ecosystems, such as the Menoreh Mountain. These crabs play an important role in the ecosystem as detrivores and a food source for other organisms. However, resesearch on their feeding habitat is still limited, leaving gaps in knowledge regarding their dietary preferences and ecological role. Understanding their feeding patterns is essential to support sustainable aquaculture and environmental conservation. The research focused on the feeding habits and food preferences of vampire crabs (Geosesarma sp.) in a humid, forested ecosystem. The study was conducted in the Menoreh Mountain region, which provides a unique habitat for these crabs. Understanding their feeding habits in this natural habitat is essential for promoting sustainable aquaculture practices, where environmental conservation is a priority. This research aimed to analyze vampire crabs’ food and feeding habits (Geosesarma sp.) in their natural habitat to support sustainable aquaculture on the Menoreh mountain slopes. The study employed frequency of occurrence analysis, volumetric analysis, and the Index of Preponderance. Sex ratio analysis and assessments of habitat conditions, including substrate texture and organic content, were conducted. The substrate consisted of sandy clay with an organic content ranging from 8.59% to 37.88%. Vampire crabs were identified as omnivores with a tendency towards herbivory, primarily consuming debris (93.47%), wood (2.75%), worms (1.92%), and leaves (1.86%). Debris was the main food source, supplemented by wood and leaf litter, with worms as an occasional food source. The findings highlighted the crabs' dietary adaptability and provided insights for future sustainable captive breeding efforts.